Técnicas de juego y su incidencia en el desarrollo de la motricidad gruesa de los estudiantes de segundo año de la Escuela de Educación Básica “Octavio Gerardo Icaza” del cantón Urdaneta, provincia los Ríos. - Ramirez Mosquera, Rubi Raquel (2017)
Through this research it is known if gross motor development has improved in the second year students of the "Eugenio espejo" Elementary School of Clemente Baquerizo parish, in this way the boy and girl strengthen their stage of development. This work also concentrates its attention on deploying a series of exercises or activities, which help to stimulate gross motor skills, as the dimensions of coordination and balance are working properly in the child to achieve valuable and meaningful learning, to guide it to maintain a stable and harmonious life with their peers. In the first instance it is necessary that the teacher be creative, this ability allows him to take advantage of all those existing elements to solve the problematic of the student community, generating new alternatives to give effective solutions to the learning problems and at the same time stimulate the creativity of his own students. The ability to be reflective and critical to assess the achievements of others allows you to determine if the objectives set have been achieved and to what extent, this is necessary as this will determine results of both the teacher's work and the progress of the children.